PEMBUDIDAYAAN JAMUR TIRAM PADA SERBUK GERGAJI DARI LIMA JENIS KAYU - Sihati Suprapti (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The result of oyster mushroom (Pleurotus ostreatus) cultivation on sawdust of five wood species i.e. jeungjing (Albizia falcataria (L.) Foeb.), rubber (Hevea brasiliensis Muell. Arg. ), pulai (Alstonia scholaris R.Br.), pine (Pinus merkusii Jungh et De Vr.) and weru (Albizia procera Benth) is reported in this paper. The compositions of the media were 97.5 % sawdust, 92.5 % sawdust + 5 % rice bran, 87.5 % sawdust +10 % rice bran, 82.5 % sawdust+ 15 % rice bran, and 77.5 % sawdust + 20 % rice bran. Each of the media was mixed with 1.5 % gypsum, 0.5 % three superphosphate (TSP), 0.5% lime and sufficient distilled water. The media was allowed to cool after sterilization before being inoculated with pure culture of mushroom. The mature mushroom were harvested daily after the growth of fruiting body. The media start producing fungus two months after inoculation. The mean yield of entire treatments were obtained from rubber: 225.86 g (146 - 261.8 g), weru : 199.28 g (23.2 - 264. 7 g), pulai: 162.4 g (67.2 - 231.2 g), jeungjing : 142.73 g (33.6 - 236.8 g) and pine : 80.97g (0 - 161.6 g) per 500 g media. The yield of mushroom cultivated. in PVC plastic bag was better than that using HD plastic bag. The rice bran supplement seems to improve mushroom yield. The average Biological Efficiency of entire treatments were obtained from weru : 90.83% (11.82-122.38 %), rubber: 88.11 % (58.04 -104.07%), pulai: 87.61% (39.38-121.38 %), jeungjing : 73.74 % (22.76-118.4 %), and pine : 28.62 % (0 - 60.6 %).